Physical and chemical quality of well water and its impact on the health of people in Sinnasippikulam in Vavuniya District, Sri Lanka - Thivyatharsan, Mr. R.; Dasinaa, Miss. S.; N. Azeeza, Miss. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
Quality ground water is important as it is the main factor determining its suitability for drinking, domestic, agricultural and industrial purposes. Scarcity of clean drinking water is being felt by billions of people around the world. Present study was conducted during 2014 to determine the ground water quality especially total hardness of water in Sinnasippikulam village which is located in Vavuniya District. In addition, a questionnaire survey was conducted to analyze the water related diseases in Sinnasippikulam village. Survey showed more than 86% of household members were not sick from Cholera and Dengue diseases over last 6 months while 8% of respondents suffered from diarrhea. Indirect  water related diseases such as skin stomach and skin rashes were with 6% and 2%, respectively. Further, around 30% of the total populations who use this water for domestic consumption were significantly identified with Chronic Kidney Disease (CKD). According to that, water samples were randomly collected from the wells located (twenty locations) in those particular area and undergone for further analysis of water specially on physical and chemical quality parameters such as total dissolved solids, electrical conductivity, pH, temperature, total hardness, nitrate and phosphate. The mean values of these parameters were recorded as pH (8.70±0.49), temperature (27.32±1.66 °C), electrical conductivity (1539.90±579.31µs/cm), total dissolved solid (753.8±294.71 mg/l), turbidity (1.23±0.80 FAU), total hardness (693.22±178.69 mg/l), phosphate (0.74±0.26 mg/l) and nitrate (3.03±1.62 mg/l). Among these parameters total hardness (693.22 mg/l) and pH (8.7) were considerably higher while comparing with the WHO permissible limits for drinking water is 200-600 and 6.5-8.5, respectively for each and also this might be a reason to the kidney problem identified through primary as well as secondary analysis in Sinnasippikulam village. It shows that to have proper consideration on well water quality while focusing its quality parameters as a health issue in future.